Fertilizantes organominerais na adubação de plantio da batata - Magela, Mara Lúcia Martins (2021)
Among the main factors influencing the development of the potato crop, as well as the achievement of high yields and quality of tubers, is the adequate supply of nutrients. Due to its characteristics (economic importance and high nutritional demand), it has been increasingly sought for sources of fertilization capable of meeting the needs of the crop, while promoting a more sustainable and efficient management. In this scenario, organomineral fertilizers represent an alternative source of fertilization for the cultivation of potatoes, as they contain an organic fraction combined with mineral sources in their composition. This constitution promotes a series of benefits for the entire production chain, from the manufacture of fertilizers to benefits for the soil-plant system. Thus, the objective of this work was to evaluate the influence of organomineral sources in the planting fertilization of Ágata, Atlantic, Asterix and Marikies cultivars in comparison with traditionally used mineral sources. Crop development was analyzed through Spad Index evaluations and leaf analysis; yield and quality of tubers, as well as soil characteristics after harvest. The experiments with the cultivars Ágata and Atlantic were carried out simultaneously in a potato production area in the city of Cristalina-GO, from June to October 2017. A causal block design with five treatments was used (100% of the recommendation for planting fertilization with mineral sources; doses of 100, 80, 60 and 40% of the recommendation with organomineral fertilizer 02-20-05) in 4 repetitions. The experiments with the cultivars Asterix and Markies were carried out in a commercial production area located in Perdizes-MG, from June to October 2018. A randomized block design with 13 treatments and 3 replications was used. The treatments consisted of combinations of planting fertilization that used mineral sources (MAP and KCl) and organominerals (05-25-00 and 00-00-30) to provide phosphorus and potassium in different doses. These doses were determined according to the mineral recommendation used by the producer (100, 80, 55, 35% of the phosphorus and potassium recommendation). It was observed that the application of organomineral fertilizers in the planting of the potato represents an alternative of fertilization for the different cultivars evaluated, promoting yield and quality results of the tubers similar and/or superior to those observed with mineral fertilizer. In addition, the chemical characteristics of the soil were maintained, making it possible to use it in the future for the next crops.